Biased covering arrays for progressive ranking and composition of Web Services. (27th July 2007) - Bryce, Renee C.; Chen, Yinong; Colbourn, Charles J.
Service-oriented computing is a new software development paradigm that allows application builders to choose from many available services. The challenges are to efficiently determine which services are the most appropriate to combine into an application based on concerns such as functionalities, licensing costs, and known reliability. Group testing has addressed some issues on how to select a small subset of candidate services. We expand upon the group testing methodology with a greedy algorithm that generates biased covering arrays for interactive testing of the services selected by group testing.